Hemotympanum as a Complication of a Valsalva Maneuver during Childbirth - Tali Teitelbaum; Isaac Shochat; Golda Grinblat; Mohamad Taha; Itzhak Braverman (Case Reports in Otolaryngology)
Background. Hemotympanum may occur due to otic barotrauma secondary to Valsalva maneuver during the second phase of labor. A pressure differential across the tympanic membrane (TM) of about five psi can cause rupture. The increased intrathoracic and intraabdominal pressure spikes repeatedly manifested by “pushing” during second-stage labor easily approach (and may exceed) this level. Clinical Presentation. This case report describes a healthy thirty-seven-year-old multipara patient admitted for the 40-weeks’ gestational age routine follow-up that proceeded to active labor followed by an aural fullness and bloody otorrhea. Otoscopic examination with a light microscope confirmed the hemotympanum of the right tympanic membrane. Conclusion. Forceful Valsalva can cause hemotympanum. Investigating the benefits and disadvantages of the pushing methods could help reduce such complications in the future. A prompt evaluation of an otolaryngologist should be requested in the event of a new postpartum hearing disturbance or bloody otorrhea.